PARTISIPASI DALAM KELAS IBU BALITA BERHUBUNGAN DENGAN PENGETAHUAN DAN SIKAP - Wanodya Hapsari; Puji Hastuti; Septerina Purwandani Winarso (Jurnal Sains Kebidanan, 2020)
This paper is carried out to assess the relationship between knowledge and attitudes towards participation in toddler mother classes. This needs to be done because participation in attending the class of under-five mothers is still low due to the customary patterns in the existing market system that most people will come to these markets on market day to meet household needs. The problem in previous research with community empowerment interventions through the use of the MCH handbook studied in the toddler mother class, was guided by the facilitator namely the midwife in the local village, but it was still not used maximally because not all mothers were willing / able to read and study it. This paper proposes exploring the relationship between knowledge of attitudes and knowledge with the participation of toddler mother classes.The method used was descriptive analytic, cross sectional, the population in this study were all mothers of toddlers aged 2-5 years as many as 1204 people, cluster sampling, a sample of 89 people, with an instrument in the form of a questionnaire. Chi square statistical test obtained attitudes and knowledge value p = 0,000 with knowledge value OR = 34.5 and attitude OR = 59.7. Conclusion: there is a significant relationship between knowledge and attitude with participation in the toddler mother class